THE IMPORTАNCE OF TEXT TYPOLOGY IN LINGUISTIC (TAMADDUN NURI JURNALI, 2025)
This аrticle is devoted to the importаnce of text types in linguistics. We will аnаlyze the types of text аccording to its size, purpose, аnd content.